MODEL PERMAINAN OBSTACLE COLOR BALL UNTUK DETEKSI DINI TUMBUH KEMBANG MOTORIK KASAR ANAK USIA 3-4 TAHUN (STUDI DI KB MULIA BUMI AGUNG LAMPUNG TIMUR) - Evi Dwi Lestari, (UNISAN JURNAL, 2024)
This research addresses the issue of early detection of early childhood development, which is still uncommon, especially in aspects of the development of children aged 3-4 years. This study aims to produce a model of the obstacle color ball game developed from the traditional game "engklek/lompat kodok" according to the characteristics of children aged 3-4 years for: 1) early detection of the development of children aged 3-4 years in KB Mulia Bumi Agung Lampung Timur, 2) determining the level of practicality of the obstacle color ball game model for early detection of the development of children aged 3-4 years in KB Mulia Bumi Agung Lampung Timur, and 3) determining the effectiveness level of the obstacle color ball game model for early detection of the development of children aged 3-4 years in KB Mulia Bumi Agung Lampung Timur. This research is a development study using the ADDIE model, consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation, with 8 subjects aged 3-4 years in KB Mulia Bumi Agung Lampung Timur. Data collection techniques used pretest-posttest observations and structured interviews with research indicators for early detection of development in terms of physical motor development with the scope of gross and fine motor skills of children aged 3-4 years in KB Mulia Bumi Agung Lampung Timur. The results show that the obstacle color ball game is "highly effective" and "very practical" for early detection of the development of children aged 3-4 years based on validity test results by experts and pretest-posttest trials and interviews. Thus, the obstacle color ball game model can be used for early detection of the development of children aged 3-4 years in KB Mulia Bumi Agung Lampung Timur. Keywords: Game Model, Early Detection of Child Development